Admission hyperglycemia and outcomes in large vessel occlusion strokes treated with mechanical thrombectomy. (13th March 2017) - Goyal, Nitin; Tsivgoulis, Georgios; Pandhi, Abhi; Dillard, Kira; Katsanos, Aristeidis H; Magoufis, Georgios; Chang, Jason J; Zand, Ramin; Hoit, Daniel; Safouris, Apostolos; Choudhri, Asim; Alexandrov, Anne W; et al.
Abstract : Background and purpose: Higher admission serum glucose levels have been associated with poor outcomes in patients with acute ischemic stroke (AIS) treated with IV thrombolysis. We sought to evaluate the association of admission serum glucose with early outcomes of patients with emergent large vessel occlusion (ELVO) treated with mechanical thrombectomy (MT). Methods: Consecutive AIS patients due to ELVO treated with MT in three tertiary stroke centers were evaluated. The following outcomes were documented using standard definitions: symptomatic intracranial hemorrhage (sICH), complete reperfusion, mortality, functional independence (modified Rankin Scale (mRS) score of 0–2), and functional improvement (shift in mRS score) at 3 months. The association of admission serum glucose and admission hyperglycemia (>140 mg/dL) with outcomes was evaluated using univariable and multivariable binary and ordinal logistic regression models. Results: 231 AIS patients with ELVO (mean age 62±14 years, 51% men, median admission National Institute of Health Stroke Scale score 16 points (IQR 12–21), median admission serum glucose 125 mg/dL (IQR 104–162)) were treated with MT. Admission hyperglycemia was associated with a lower likelihood of functional improvement (common OR 0.53; 95% CI 0.31 to 0.97; p=0.027) and higher odds of 3 month mortality (OR 2.76; 95% CI 1.40 to 5.44; p=0.004) in multivariable analyses adjusting for potential confounders. A 10 mg/dL increase in admission blood glucose was associated with a higher likelihood of sICH (OR 1.07; 95% CI 1.01 to 1.13; p=0.033) and 3 month mortality (OR 1.07; 95% CI 1.02 to 1.12; p=0.004) in multivariable models. There was no association between admission serum glucose or hyperglycemia and complete reperfusion. Conclusions: Higher admission serum glucose and admission hyperglycemia are independent predictors of adverse outcomes in ELVO patients treated with MT.